2015
DOI: 10.15184/aqy.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Using experimental archaeology and micromorphology to reconstruct timber-framed buildings from Roman Silchester: a new approach

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…If it was an outdoor area, the sediment would be more homogenous and microartefacts would be embedded in it (W. Matthews, 2003; Rentzel et al, 2017; Shillito & Ryan, 2013; Wouters et al, 2017). However, there are no traces of domestic activities such as in situ microartefacts (defacto waste according to Schiffer, 1972) or occupation layers rich in charcoal fragments and ash—as would be typical for indoor areas—to be found (Banerjea, Fulford, Bell, Clarke, & Matthews, 2015; Gé, Courty, Matthews, & Wattez, 1993; W. Matthews, 2003, 2012; Rentzel et al, 2017). Regular cleaning of the floors or the use of mats or the like to cover the floor might explain this.…”
Section: Discussionmentioning
confidence: 99%
“…If it was an outdoor area, the sediment would be more homogenous and microartefacts would be embedded in it (W. Matthews, 2003; Rentzel et al, 2017; Shillito & Ryan, 2013; Wouters et al, 2017). However, there are no traces of domestic activities such as in situ microartefacts (defacto waste according to Schiffer, 1972) or occupation layers rich in charcoal fragments and ash—as would be typical for indoor areas—to be found (Banerjea, Fulford, Bell, Clarke, & Matthews, 2015; Gé, Courty, Matthews, & Wattez, 1993; W. Matthews, 2003, 2012; Rentzel et al, 2017). Regular cleaning of the floors or the use of mats or the like to cover the floor might explain this.…”
Section: Discussionmentioning
confidence: 99%
“…7e), with unoriented clays and lack of laminations or layering, are present in unit at the base of unit 401c (thin section 5), in unit 401b (thin section 4), and in and 401a (thin section 1). These textural pedofeatures might confirm the dumping of loose material or might derive also from post-depositional modification (such as decay of organics or changes in redox conditions-see Banerjea et al 2015aBanerjea et al , 2015b. Vivianite crystal intergrowths are attested throughout the sequence, with the exception of unit 402 (Fig.…”
Section: Sequence Imentioning
confidence: 88%
“…That strip buildings should be included among the individually owned residences is supported by excavations at Cirencester, Verulamium and other sites across the Roman world. As Holbrook notes, 'It is a commonplace derived from well-preserved sites such as Pompeii and Ostia that the front part of the building facing the street served as the shop area, with workshop and living accommodation to the rear 33 Lobo et al 2020. 34 Banerjea et al 2015 have suggested a method for reconstructing the architectural designs of timber-framed and earthen-walled structures at Silchester based on a combination of experimental archaeology and micromorphology. Unfortunately, this method can only be applied to recently excavated areas, so it cannot be used to estimate the overall numbers of timber structures at the site.…”
Section: Introductionmentioning
confidence: 99%
“… 34 Banerjea et al 2015 have suggested a method for reconstructing the architectural designs of timber-framed and earthen-walled structures at Silchester based on a combination of experimental archaeology and micromorphology. Unfortunately, this method can only be applied to recently excavated areas, so it cannot be used to estimate the overall numbers of timber structures at the site.…”
mentioning
confidence: 99%